قياس الشبه و اثره في اختلاف الفقهاء - ايناس هادي; ماريا مغاربي; د/محمد علالي (جامعة عمار ثليجي الاغواط, 2024)
الملخص : تناول هذا البحث دراسة نوع مهمّ من أنواع القياس الأصوليّ ، وهو قياس الشبه ،الذي كثُر التعويل عليه لاتساع معناه . إذ يعدّ من الأقيسة الغامضة التي تحتاج إلى توضيح و بيان.و قد جاء هذا البحث بغرض بيان مدى أهمية قياس الشبه نظرًا للغموض و الإبهام الذي يصاحبه ، فقُسم البحث إلى فصلين نظري و تطبيقي، و تمّ في هذه الدراسة الكشف عن ماهية قياس الشبه ، وتوضيح الفرق بينه و بين ما يشابهه ، كما يستعرض البحث إبراز أهم الشروط و الضوابط الضامنة لسلامة الإستدلال بالشبه ، إضافة إلى كونالأصوليون لم يتفقوا على حقيقة قياس الشبه فقد اختلفوا في حجّيته و في ظل ذلك اختلفوا على مذاهب بين مثبتين و منكرين ،وقد كشفت الدراسة رجحان مذهب الجمهور القائل بحجيّته . وقد تطرقنا في الجزء التطبيقي للدراسة إلى سرد بعض الفروع الفقهية في بابي الطهارة و الصلاة ، التي كان لقياس الشبه أثرٌ بشأنها. الكلمات المفتاحية : القياس ، الشبه ، الآثار الفقهية . Abstract : This research examined an important type of fundamentalist measurement, the analogy measurement, which is often relied upon for its breadth, as it is one of the ambiguous aisles that needs clarification and articulation. This research was designed to demonstrate the importance of measuring the likeness due to the ambiguity and thumb that accompanies it, and the research was divided into two theoretical and applied chapters. This study revealed what measurement of the likeness is, and illustrated the difference between it and what it is like. The research also reviews the highlight of the most important conditions and safeguards for the integrity of the reasoning of the likeness, as well as the fact that Fundamentalists did not agree on the fact that the analogy was measured, they disagreed in his argument, and in doing so they disagreed on doctrines between proven and denying, and the study revealed the preponderance of the audience's doctrine that it was authentic. In the applied part of the study, we touched on the account of some of the jurisprudence branches in the doors of purity and prayer, about which measurement of the likeness had an effect. Keywords: measurement, resemblance, jurisprudence effects.
باب الطهارة و الصلاة - انموذجا